IMPLEMENTASI METODE TALAQQY DALAM MENINGKATKAN KUALITAS HAFALAN BAHASA ARAB MATERI MUFRODAT DI SMPIT AL-JABAR - Winda Rizkya Lestari; Agus Fudholi; Haerudin (LP2M IAIN Sultan Amai Gorontalo, 2026)
This study aims to analyze the application of the talaqqy method in improving the quality of Arabic memorization of mufrodat material among seventh-grade students of SMPIT Al-Jabar. The research method used is qualitative with a descriptive type. Data collection techniques include interviews, observation, and documentation. Meanwhile, data analysis techniques are carried out through data presentation, data reduction, and drawing conclusions. The research results were obtained from learning observations, interviews with Arabic language teachers, interviews with six students, and supporting documentation. The results of this study indicate that the talaqqy method is implemented through the steps of listening, imitating, and repeating the vocabulary words directly with teacher guidance. The implementation of this method has a positive impact on students' vocabulary memorization abilities, as shown by improvements in correct pronunciation, better memory, and increased self-confidence and motivation to learn. However, in practice, there are still several obstacles and shortcomings such as students' ability to absorb and imitate different vocabulary words, limited lesson time, large number of students, and also variations in student concentration levels. Overall, the talaqqy method has proven effective as an alternative learning strategy to improve the quality of Arabic vocabulary memorization at the junior high school level, with the note that the need for more optimal classroom management and time management.